Design And Implementation Of Motion Sensitive UHF RFID System - Hamid, Shabinar Abdul (2011)
Radio Frequency Identification (RFID) is a method of remotely storing and retrieving data using devices called RFID tags. RFID system components comprise of RFID tag and RFID reader. The RFID tag stores a unique identification of the object that is attached to it. However, it does not provide information about the conditions of the object that it detects. Sensor node in Wireless Sensor Network (WSN), on the other hand, provides information about the condition of the object and its environment. Therefore, with the integration of RFID and WSN technology, their disadvantages can be overcome and their advantages can be put into some important applications.